The genius of design by Chris Wilson; Denis Lawson; Anthony Burke; Wall to Wall Media.; Acorn Media (Firm); et al. - Wilson, Chris (Distributed by Acorn Media, 2010)
Every aspect of modern life is influenced by industrial design, from office chairs to apartment complexes. This fascinating series delves into the personalities and technology that shape the world's environment, economy, and culture.